Dysfunction of the glymphatic system in childhood absence epilepsy - Pu, Wanqing; Wei, Shanzhen; Qiu, Mengdi; Chen, Xiaoyu; Zou, Wenwei; Ge, Yingchao; Qiu, Wenchao (Frontiers in Neuroscience, 2023)
Objective This study aimed to evaluate the glymphatic system in childhood absence epilepsy (CAE) using diffusion tensor image analysis along the paravascular space (DTI-ALPS) index. Methods: Forty-two CAE patients and 50 age- and gender-matched healthy controls (HC) were included in this study. All participants underwent scanning using a Siemens 3.0 T magnetic resonance scanner, and the DTI-ALPS index was calculated. The study compared the differences of DTI-ALPS index between CAE patients and the healthy controls. Additionally, this study also assessed the relationship between the DTI-ALPS index and clinical characteristics such as age, seizure frequency, and duration of epilepsy. Results The DTI-ALPS index was lower in CAE patients compared to the healthy controls (1.45 ± 0.36 vs. 1.66 ± 0.30, p < 0.01). The DTI-ALPS index showed a negative correlation with the duration of epilepsy (r = −0.48, p < 0.01) and a positive correlation with age (r = 0.766, p < 0.01) in CAE patients. However, no significant correlation was observed between the DTI-ALPS index and seizure frequency. Conclusion The results of this study indicate that children with CAE exhibit dysfunction in the glymphatic system of the brain, which might contribute to understanding the pathophysiological mechanism of CAE. The DTI-ALPS, as a non-invasive diagnostic marker, can be used to assess the function of the glymphatic system in CAE patients, providing promising applications in the diagnosis and research of CAE.